2018
DOI: 10.1016/j.jval.2018.01.016
|View full text |Cite|
|
Sign up to set email alerts
|

Advocating a Paradigm Shift in Health-State Valuations: The Estimation of Time-Preference Corrected QALY Tariffs

Abstract: Our results highlight the relevance and even necessity of a paradigm shift in health valuation studies in favor of time-preference corrected QALY tariffs, with potentially important implications for health technology assessment calculations and regulatory decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 35 publications
(40 reference statements)
0
25
2
Order By: Relevance
“…Time-preference-corrected quality-adjusted life year (QALY) tariffs avoid confounding between quality of life and time preferences without resulting in time-dependent QALY tariffs. 1 In nominal terms, each QALY still represents 1 year in perfect health, which conforms to the conventional QALY assumptions. However, when QALYs are compared across time, they can and should be discounted to properly reflect time preferences.…”
Section: Introductionmentioning
confidence: 74%
“…Time-preference-corrected quality-adjusted life year (QALY) tariffs avoid confounding between quality of life and time preferences without resulting in time-dependent QALY tariffs. 1 In nominal terms, each QALY still represents 1 year in perfect health, which conforms to the conventional QALY assumptions. However, when QALYs are compared across time, they can and should be discounted to properly reflect time preferences.…”
Section: Introductionmentioning
confidence: 74%
“…One area in particular is the assumption of linear time preferences and how this may violate basic human behavior. Recent studies have shown that allowing for nonlinear time preferences, through the use of discounting functions, provides a better statistical fit [6,15]. These differences could lead to misallocation of resources and incorrect implementation of interventions against COVID-19 depending on which value set is chosen.…”
Section: Discussionmentioning
confidence: 99%
“…The choice sets will be explained as textual and visual scenarios. We will use visual elements to reduce the likelihood of possible dropping due to choice set complexity or illiteracy that will help participants to quickly identify the levels [ 23 , 40 , 41 ]. An example of a DCE choice task is shown in Fig.…”
Section: Study Design/methodsmentioning
confidence: 99%